A comparison between palonosetron and ondansetron in prevention of postoperative nausea and vomiting after laparoscopic cholecystectomy (Mediscope, 2015)
Postoperative nausea and vomiting (PONV) are common complications after anesthesia and surgery and is associated with adverse outcome. This study was designed to compare the effects of palonosetron and ondansetron in preventing PONV in patients with laparoscopic cholecystectomy. This prospective double-blind study included 60 female patients randomly assigned to the palonosetron group (n = 30) or the ondansetron group (n = 30). Palonosetron 0.075 mg was injected intravenously as a bolus in the palonosetron group. Ondansetron 8 mg was injected intravenously as a bolus in the ondansetron group. The incidences of nausea and vomiting and side effects was recorded after 30 min, 60 min, 2 hrs, 8hrs, 24 hrs postoperatively. The incidence of nausea and vomiting was maximal during immediate postoperative period particularly initial 4 hrs of postoperative period. The complete control of postoperative nausea and vomiting was seen in 30% patients of ondansetron group in first 12 hrs of postoperative period and 90% in palonosetron group. Safety profile was more with palonosetron. The effects of palonosetron and ondansetron in preventing PONV were compared in patients undergoing laparoscopic cholecystectomy and it was found that palonosetron was better in preventing postoperative nausea and vomiting.Mediscope Vol. 2, No. 2: July 2015, Pages 33-38